Effect Of Stone Crusher Dust On Some Macro- And Micro Nutrients And Biochemical Parameters Of Some Selected Tree Species In Central Kashmir (India) (Applied Biological Research, 2023)
Stone crushing process leads to the emission of huge dust which depletes soil  quality and adversely affects the plant growth and development. The present  study was aimed to assess the impact of stonecrusher dust on nutrient content  and biochemical status of leaves of four widely growing tree species viz. Salix  alba, Robinia pseudoacacia, Populus deltoides, and Ailanthus excels in districts Srinagar and Budgam of Kashmir. Leaf samples were collected both from the  disturbed and undisturbed sites in separate polythene bags and analysed for  micro-and macro nutrients, photosynthetic pigments, carotenoid and ascorbic  acid contents. The results revealed low nitrogen content (1.90% in S. alba),  phosphorus (0.15% in A. excelsa), potassium (0.25% in R. pseudoacacia) and  photosynthetic pigments (total chlorophyll 1.26 mg g-1in A. excelsa), and  carotenoid (0.06 mg kg-1in A. excelsa) at disturbed sites of Srinagar and  Budgam; while higher contents were recorded at respective control sites. The  highest content (in mg kg-1) of Fe (61.54, in S. alba), Mn (38.23, in P. deltoides),  Cu (27.54 in P. deltoides), Zn (37.16, in P. deltoides) and ascorbic acid (7.93, in S.  alba) was recorded in disturbed site. The study revealed that stone crusher dust  dversely affects the leaf physiology, and two plant species viz., S. alba and P.  deltoids showed some degree of tolerance todust pollution.
Keywords: Ailanthus excels; biochemical parameters; nutrients; Populus deltoides; Robinia pseudoacacia; Salix alba; stone dust